PENYIDIKAN TERHADAP KONFLIK ANTARA DESA KABUN DAN DESA ALIANTAN DI WILAYAH HUKUM KEPOLISIAN RESOR KABUPATEN ROKAN HULU - Rido Hamidi; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Social conflict can be caused by many things , namely the establishment of adifference, cultural background differences, different interests and groups, rapidchanges in social values in society, socio-economic disparities that exist. Socialconflicts in society can lead to a loss in one or all parties involved in the conflict,where this can be a material and moral damage. For example casualties in theconflict between the village and the village Kabun Aliantan, both injuries andeven fatalities can be contained. Based on this understanding, then writing thisessay to formulate two formulation of the problem, namely : First, how theinvestigation of the conflict between the Village and the Village Aliantan KabunTerritory Police Law Rokan Hulu ? Secondly, what are the obstacles in theprocess of the interrogation of the conflict between the Village and the VillageKabun Aliantan Territory Police Law Rokan Hulu ?Keywords : Investigation - Conflict - Inter- village